2004
DOI: 10.1158/1078-0432.ccr-03-0157
|View full text |Cite
|
Sign up to set email alerts
|

The Role of α-Folate Receptor-Mediated Transport in the Antitumor Activity of Antifolate Drugs

Abstract: Conclusions: Antifolate drugs, particularly ZD9331, have the potential for increased efficacy in tumors that highly overexpress the ␣-FR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 40 publications
1
61
0
1
Order By: Relevance
“…Methotrexate primarily targets dihydrofolate reductase, raltitrexed targets thymidylate synthase and the more recently introduced pemetrexed has multiple targets in the folate pathway. The role of FRa in the uptake of both folates (essential for cellular purine and pyrimidine biosynthesis and eventually DNA synthesis) and antifolates has been the subject of numerous publications with contrasting results (Chattopadhyay et al, 2004;Theti and Jackman, 2004). Chemotherapy for mesothelioma, using pemetrexed and platinum, is now the standard treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methotrexate primarily targets dihydrofolate reductase, raltitrexed targets thymidylate synthase and the more recently introduced pemetrexed has multiple targets in the folate pathway. The role of FRa in the uptake of both folates (essential for cellular purine and pyrimidine biosynthesis and eventually DNA synthesis) and antifolates has been the subject of numerous publications with contrasting results (Chattopadhyay et al, 2004;Theti and Jackman, 2004). Chemotherapy for mesothelioma, using pemetrexed and platinum, is now the standard treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…Similar differences in pemetrexed sensitivity have also been reported (Chattopadhyay et al, 2006) between H28 andH2052 cells (GI 50 values 90 and40 nM, respectively). It has been reported that the effect of pemetrexed is enhanced in cell lines when there is a low or physiological concentration of folate in the medium (Theti and Jackman, 2004) and that higher extra-cellular folate levels correlate inversely with pemetrexed activity in vitro in mesothelioma and other solid tumour cell lines (Chattopadhyay et al, 2007). In our studies, it was found that when using normal or lowfolate medium (results using low-folate medium are not shown) and dialysed or normal serum, the main difference in the effect of pemetrexed was seen between the dialysed serum and normal serum as reported here; hence, low-folate medium was not routinely used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differential expressions offer the development of diagnostic agents and folate receptor-mediated tumor targeted therapy in the treatment of various cancers (Theti and Jackman, 2004). Disruption of folate metabolism has long been known to inhibit cell growth and has been established as a target in chemotherapy with the use of antifolates (Brzezinska et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This drug is a relatively poor substrate for FPGS compared to RTX . Fourthly, a-folate receptor (a-FR) mediated uptake may contribute to the activity of some antifolates, particularly BGC9331 (Theti and Jackman, 2004). The a-FR is overexpressed in up to 90% of epithelial ovarian cancers (Toffoli et al, 1997).…”
Section: Bgc9331 In Ovarian Cancermentioning
confidence: 99%